Correlated Lattice Instability and Emergent Charged Domain Walls at Oxide Heterointerfaces. (26th September 2019) - Li, Mengsha; Huang, Zhen; Tang, Chunhua; Song, Dongsheng; Mishra, Tara Prasad; Ariando, Ariando; Venkatesan, Thirumalai; Li, Changjian; Pennycook, Stephen J.
Abstract: Charged domain walls provide possibilities in effectively manipulating electrons at nanoscales for developing next‐generation electronic devices. Here, using the atom‐resolved imaging and spectroscopy on LaAlO3 /SrTiO3 //NdGaO3 heterostructures, the evolution of correlated lattice instability and charged domain walls is visualized crossing the conducting LaAlO3 /SrTiO3 heterointerface. When increasing the SrTiO3 layer thickness to 20 unit cells and above, both LaAlO3 and SrTiO3 layers begin to exhibit measurable polar displacements to form a tail‐to‐tail charged domain wall at the LaAlO3 /SrTiO3 interface, resulting in the charged redistribution within the 2‐nm‐thick SrTiO3 layer close to the LaAlO3 /SrTiO3 interface. The mobile charges in different heterostructures can be estimated by summing up Ti 3+ concentrations in the conducting channel, which is sandwiched by SrTiO3 layers with interdiffusion and/or oxygen octahedral rotations. Those estimated mobile charges are quantitatively consistent with results from Hall measurements. The results not only shed light on complex oxide heterointerfaces, but also pave a new path to nanoscale charge engineering. Abstract : Charged domain walls in non‐ferroelectric materials open a much wider choice of materials for domain wall‐based device engineering. By scanning transmission electron microcopy and electron energy loss spectroscopy, tail‐to‐tail charged domain walls, are revealed in LaAlO3 /SrTiO3 //NdGaO3 heterostructures. The strong correlation between the domain wall and interface interdiffusion, plus oxygen octahedral rotation determine the complicated SrTiO3 thickness dependent transport properties.